The Integral Role of Genetic Variation in the Evolution of Outcrossing in the Caenorhabditis elegans-Serratia marcescens Host-Parasite System - Parrish, Raymond C. (PLoS One, 2016)
Outcrossing is predicted to facilitate more rapid adaptation than self-fertilization as a result of genetic exchange between genetically variable individuals. Such genetic exchange may increase the efficacy of selection by breaking down Hill-Robertson interference, as well as promoting the maintenance of within-lineage genetic diversity. Experimental studies have demonstrated the selective advantage of outcrossing in novel environments. Here, we assess the specific role of genetic variation in the evolution of outcrossing. We experimentally evolved genetically variable and inbred populations of mixed mating (outcrossing and self-fertilizing) Caenorhabditis elegans nematodes under novel ecological conditions—specifically the presence of the virulent parasite Serratia marcescens. Outcrossing rates increased in genetically variable host populations evolved in the presence of the parasite, whereas parasite exposure in inbred populations resulted in reduced rates of host outcrossing. The host populations with genetic variation also exhibited increased fitness in the presence of the parasite over eight generations, whereas inbred populations did not. This increase in fitness was primarily the result of adaptation to the parasite, rather than recovery from initial inbreeding depression. Therefore, the benefits of outcrossing were only manifested in the presence of genetic variation, and outcrossing was favored over self-fertilization as a result. As predicted, the benefits of outcrossing under novel ecological conditions are a product of genetic exchange between genetically diverse lineages.